2013
DOI: 10.1080/08897077.2013.781564
|View full text |Cite
|
Sign up to set email alerts
|

Self-Forgiveness, Shame, and Guilt in Recovery from Drug and Alcohol Problems

Abstract: Background: People with drug and/or alcohol problems often experience feelings of shame and guilt, which have been associated with poorer recovery. Self-forgiveness has the potential to reduce these negative experiences. Methods: The current study tested theorized mediators (acceptance, conciliatory behavior, empathy) of the relationships between shame and guilt with self-forgiveness. A cross-sectional sample of 133 individuals (74.4% male) receiving residential treatment for substance abuse completed self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 51 publications
7
42
1
10
Order By: Relevance
“…In a clinical sample, McGaffin et al (2013) found a positive unique link between overall guilt-proneness and self-forgiveness, a finding that is consistent with the theoretical perspectives outlined above. Still, in undergraduate samples, Rangganadhan and Todorov (2010) did not find a unique association, and Strelan (2007) found a small negative link.…”
Section: Role Of Guilt-proneness In Self-forgivenesssupporting
confidence: 72%
See 3 more Smart Citations
“…In a clinical sample, McGaffin et al (2013) found a positive unique link between overall guilt-proneness and self-forgiveness, a finding that is consistent with the theoretical perspectives outlined above. Still, in undergraduate samples, Rangganadhan and Todorov (2010) did not find a unique association, and Strelan (2007) found a small negative link.…”
Section: Role Of Guilt-proneness In Self-forgivenesssupporting
confidence: 72%
“…For Sample 2, we replaced the Howell et al measure with a post-transgression repair measure used in past self-forgiveness research, which includes additional conciliatory behaviors (e.g., apology, amends, etc. ), more consistent with self-forgiveness theory (Rangganadhan & Todorov, 2010;McGaffin et al, 2013).…”
Section: Samplesupporting
confidence: 69%
See 2 more Smart Citations
“…Likewise, forgiveness has been observed to be associated with acceptance (McGaffin, Lyons, & Deane, 2013) and mindfulness (Webb, Phillips, et al, 2013).…”
Section: Acceptance-based Modalitiesmentioning
confidence: 96%